The Healthcare Workers’ Perception Regarding the Impact of Nyaope Drug and Alcohol Use on Tuberculosis Patients in Limpopo Province, South Africa - Hulisani Matakanye; Takalani Grace Tshitangano (KHD-Production, 2024)
Illicit drug and alcohol use disorder have negative impact on treatment adherence and are associated with the discontinuation of tuberculosis treatment which is a barrier to tuberculosis control. They significantly increase the risk of poor treatment outcomes in both drug-susceptible and multidrug-resistant tuberculosis patients. The main aim of this study was to explore Health care workers’ perception regarding the impact of Nyaope drug and alcohol use on Tuberculosis Patients in Limpopo Province, South Africa. The study used exploratory qualitative design. Purposive sampling method was used to sample sixteen participants (TB focal person and eight facility operational managers) who signed consent form. Data were collected through key informant in-depth interviews. Data were analysed using Colaizzi's method. Trustworthiness was ensured and ethical considerations were observed. The results show four individual major themes that emerged from data analysis: (1) Patients forget to take treatment, (2) Patients miss follow up visit and DOT support appointments (3) Patients refuse social support (4) Patients refuse to attend health education and counselling. The study highlighted the impact of Nyaope and alcohol abuse on TB treatment adherence among TB patients. There is a need to integrate treatment for alcoholism and drug addiction into primary health care to identify specific patients suffering from alcoholism and drug addiction on time. The successful identification of Nyaope drug users and alcohol abusers in these communities is an important component of a comprehensive TB strategy. Failure to do so, shows a missed opportunity with serious clinical and public health implications.